Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 3 - Equations and Problem Solving - 3.3 - More on Solving Equations and Problem Solving - Problem Set 3.3 - Page 114: 27



Work Step by Step

Using the properties of equality and combining like terms, the value of the variable that satisfies the given equation, $ 5n-4-n=-3n-6+n ,$ is \begin{array}{l}\require{cancel} 5n-n+3n-n=-6+4 \\\\ 6n=-2 \\\\ n=\dfrac{-2}{6} \\\\ n=-\dfrac{\cancel{2}}{\cancel{2}\cdot3} \\\\ n=-\dfrac{1}{3} .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.